PENGARUH PENAMBAHAN FLY ASH DAN BOTTOM ASH PADA PEMBUATAN BETON MUTU F’C 20 MPA DALAM UPAYA PEMANFAATAN LIMBAH INDUSTRI - -, Kusdiyono; -, Supriyadi; Wahyono, Herry Ludiro (Politeknik Negeri Semarang, 2017)
Fly ash and bottom ash are solid waste generated by coal combustion in steam power plants or other industrial processes. This solid waste is present in a relatively large amount, requiring serious management to avoid causing environmental pollution problems, such as air pollution, waters and other ecosystem degradation. The phenomenon that occurs, the handling of this waste is not maximal, it is proven that there are still companies dumping coal ash in the Southern Ring Road of Salatiga city (Suara Merdeka, 2012), coal waste feeding victims at Kayen Pati (Sura Merdeka, 2012), events like this show That the solid waste management from industry is not well managed. While research in the field of Materials Engineering has been done by researchers as an effort to solve problems and utilize this industrial waste to be produced into other industries such as building materials. The results showed that the quality of Concrete with model / type B10 s.d. B17.5 there is an increase in average compressive strength. Hightst increase in fly ash and bottom ash 12.5% with average compressive strength reaching 36.09 N / mm² age of 3 days, while decrease occurred in addition of fly ash and bottom ash to 20% with decrease of compressive strength of lowest average 28.03 N / mm² at 28 day test age. The regression equation obtained Y = - 0,181 X² - 2,367 X + 24,50 with correlation value R² = 0,886, it means with addition of fly ash and bottom ash have very strong influence to compressive strength of concrete. So we get an illustration that by adding fly ash and bottom ash on the manufa ture of concrete and the quality of concrete to be better.Kata Kunci: fly ash and bottom ash, pollution, concrete